Developing a protocol to identify and prioritize research questions for psoriasis: a James Lind Alliance Priority Setting Partnership. (31st March 2018) - Majeed‐Ariss, R.; McPhee, M.; Bundy, C.; Griffiths, C.E.M.; Young, H.
Summary: Background: Psoriasis affects over two million people in the U.K. It has a significant psychological and social impact on individuals and an associated high economic cost to the U.K. National Health Service. There are many unanswered questions about psoriasis. Objectives: To develop a protocol in order to work with patients, families, carers and healthcare professionals to identify psoriasis uncertainties; to agree by consensus a top‐10 list of psoriasis uncertainties; and to disseminate prioritized unanswered questions to researchers and funders so as to promote work that will focus on answering the uncertainties considered most important by stakeholders. Methods: A Psoriasis Priority Setting Partnership has been established to gather psoriasis uncertainties following the transparent methodology advocated by the James Lind Alliance. A steering group composed of stakeholders has disseminated an initial survey to patients, families, carers and healthcare professionals to collect information on important psoriasis questions. After removing duplications, uncertainties will be collated and checked against existing evidence to determine whether any have already been resolved. 'True uncertainties' will be circulated to stakeholders in a second survey where they will be ranked by importance. At a final workshop, information will be distilled to generate a top‐10 list of uncertainties. Results: By following the protocol outlined in this paper a prioritized list of uncertainties will be identified that will be used to inform the psoriasis research agenda. Conclusions: Research targeted to address priorities identified by a range of stakeholders is imperative. This project will inform policy makers and research funding bodies about what really matters to these groups. Abstract : What's already known about this topic? Psoriasis is a common immune‐mediated inflammatory skin disease affecting over two million people in the U.K. Psoriasis has an economic cost to the U.K. National Health Service of £500 million per annum. Access to appropriate care can be poor for people with psoriasis who often experience high levels of psychological distress, complex social needs and interconnected physiological symptoms. Many unanswered questions about psoriasis remain. What does this study add? The Psoriasis Priority Setting Partnership is working with patients, their families, carers and healthcare professionals to develop a protocol in order to identify uncertainties about psoriasis and its management. A top‐10 list of uncertainties will be agreed by consensus. This list will be disseminated to researchers and funders to promote research on those questions that patients, families, carers and healthcare professionals consider most important. Plain language summary available online Respond to this article